PM2.5 Synergizes With Pseudomonas aeruginosa to Suppress Alveolar Macrophage Function in Mice Through the mTOR Pathway - Zhang, Jianlong; Liu, Chong; Zhao, Guangrong; Li, Meng; Ma, Di; Meng, Qingguo; Tang, Wenli; Huang, Qingrong; Shi, Peimin; Li, Youzhi; Jiang, Linlin; Yu, Xin; et al. (Frontiers in Pharmacology, 2022)
High concentrations of PM2.5 in enclosed broiler houses cause respiratory disorders in humans and animals. Pseudomonas aeruginosa (P. aeruginosa) is an opportunistic pathogen that can induce severe respiratory disease in animals under stress or with abnormal immune functions. Alveolar macrophages are lung-resident immune cells that play important roles in lung host defence and immune balance. In this study, the mechanism by which PM2.5 synergizes with P. aeruginosa to damage alveolar macrophage function and induce inflammation was investigated. The results will provide a theoretical basis for improving the poultry breeding environment and preventing the recurrence of infection with P. aeruginosa. Alveolar macrophages were stimulated by PM2.5 collected in an enclosed broiler house and P. aeruginosa. Phagocytosis was determined by the neutral red test. The apoptosis rate and cytoskeleton changes were observed by flow cytometry assays and laser scanning confocal microscopy. Protein levels related to autophagy and the mTOR pathway were detected by Western blotting. The results indicated that PM2.5 in combination with P. aeruginosa could decrease phagocytosis, inhibit autophagy, increase apoptosis, and destroy the cytoskeleton in alveolar macrophages. In addition, alveolar macrophages had significantly increased expression of mTOR pathway-related proteins in response to the synergistic stimulation of PM2.5 and P. aeruginosa. The above results confirmed that PM2.5 in poultry houses synergized with P. aeruginosa to impede alveolar macrophage function and caused more severe respiratory system injuries through a process closely related to the activation of the mTOR signalling pathway.